2006
DOI: 10.1111/j.1467-6427.2006.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa: treatment satisfaction

Abstract: Patient satisfaction plays a central role in treatment alliance and outcome. Investigating patient expectations and experiences of treatment sheds light on its importance. This study examines adolescent anorexia nervosa patients and their parents' satisfaction with family-based treatment. Patients and parents answered a questionnaire at the eighteen-month follow-up focusing on expectations and experiences of treatment, therapists, aims of treatment and accomplishment. The results show that 73 per cent of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
(19 reference statements)
5
25
0
Order By: Relevance
“…46 Our results indicate that both parents found it valuable to be involved in their child's treatment, by staying with her during hospitalization and participating in family therapy sessions. The high level of parental satisfaction with family therapy in adolescent AN is consistent with the studies of Krautter and Lock 12 and Paulson-Karlsson et al 14 In Norway, parents are entitled to sick leave with full salary to care for severely ill children under the age of 18. This helped to make their participation economically and practically possible.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…46 Our results indicate that both parents found it valuable to be involved in their child's treatment, by staying with her during hospitalization and participating in family therapy sessions. The high level of parental satisfaction with family therapy in adolescent AN is consistent with the studies of Krautter and Lock 12 and Paulson-Karlsson et al 14 In Norway, parents are entitled to sick leave with full salary to care for severely ill children under the age of 18. This helped to make their participation economically and practically possible.…”
Section: Resultssupporting
confidence: 77%
“…Surprisingly, we have found only four studies assessing parent satisfaction in adolescent AN treatment, [12][13][14]16 and there are no comparisons of satisfaction between mothers and fathers. In the present study, both parents participated closely in the treatment and daily care of the patient, allowing us to assess and compare parents' perception of treatment.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The context of child and adolescent psychiatry includes the challenge of working with both children and adults (Kazdin 2004). A follow-up study of treatment satisfaction of adolescents suffering from anorexia nervosa and their parents showed that parents were more pleased with the therapists than were their children (Paulson-Karlsson et al 2006). Indeed, it has been found that the voice of the child tends to become secondary in family therapy settings (Cederborg 1994).…”
Section: Introductionmentioning
confidence: 97%
“…Separated FBT has the potential to overcome some of the perceived challenges or deficiencies of conjoint FBT and so may be preferred by some families. In practice, separated FBT has been shown to be acceptable to families and to meet patient and parent expectations (Paulson-Karlsson, Nevonen, & Engström, 2006).…”
Section: Separating Parents and Adolescents In Treatment For Anmentioning
confidence: 99%